A POSTCOLONIAL CRITICAL ASSESSMENT OF THE IMAGO DEI IN GEN 1:26-281 IN NIGERIAN PERSPECTIVE - Ahiamadu, Amadi (Scriptura, 2010)
The concept of 'subdue the earth' and of 'dominion' given a literal interpretation in the Priestly text of Gen 1:1-2:4a is linked to an interpretation of the 'Imago Dei' or the image likeness of God in Gen 1:26-28 to mean that humans occupy the unique role of 'rulers' of the earth under God. It has served the West as the 'magna carta' of imperial rule and neocolonial domination. A critical exegesis of the concept of 'subdue' and 'rule' in especially Gen 1:28 do reveals a more liberating conception of 'imago Dei' with implications for human rule and dominion. In this paper I have attempted to critically assess the imago Dei from the point of view of archaeology and Old Testament postcolonial critical exegesis through a re-reading of Gen 1:28 which, with an Ogba (African) based world-view, provides new insights for addressing the problem of oil exploration, exploration and exploitation in Nigeria's Niger Delta.